2018
DOI: 10.5004/dwt.2018.22487
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on seasonal variation in hydro-chemical parameters of Ganga River water using comprehensive pollution index (CPI) at Rishikesh (Uttarakhand) India

Abstract: The assessment of the Ganga River System at Rishikesh was investigated at five different sites for three different seasons (summer, winter and monsoon) using comprehensive pollution index (CPI), considering 10 physicochemical parameters such as conductivity, turbidity, total dissolved solids, dissolved oxygen, biochemical oxygen demand, chemical oxygen demand, total hardness, Cl, phosphate and sulphate. The CPI was found to be 0.54 2.47, which indicates the variation in pollution level of the River Ganga. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 7 publications
1
9
1
Order By: Relevance
“…The values of K + recorded in this study were within the results range obtained by Anyanwu (2012). However, some recent studies on fresh waters (Matta et al, 2018;Anyanwu and Ukaegbu, 2019) reported quite lower K + values compared to the values recorded in this study.…”
Section: Physical-chemical Parameterscontrasting
confidence: 84%
“…The values of K + recorded in this study were within the results range obtained by Anyanwu (2012). However, some recent studies on fresh waters (Matta et al, 2018;Anyanwu and Ukaegbu, 2019) reported quite lower K + values compared to the values recorded in this study.…”
Section: Physical-chemical Parameterscontrasting
confidence: 84%
“…The same kind of trend was observed in many works on river Ganga [54][55][56][57]. A significant influence of environmental factors on seasonal distribution of water quality parameters in river was reported [58]. During rainy season, the dilution effect for surface run-off may be responsible for changing the concentration of pollutants and reduction of its value [59,60].…”
Section: Plos Watersupporting
confidence: 71%
“…In this regard, various developmental activities (i.e. construction of roads and dams at the upstream region of the Himalayas) and discharge of agricultural wastes in the river reported as critical sources of contaminations (Matta et al 2018c(Matta et al , 2020c.…”
Section: Introductionmentioning
confidence: 99%